TINJAUAN ATAS PEMENUHAN KEWAJIBAN PAJAK PERTAMBAHAN NILAI PADA KOPERASI KARYAWAN PT. ABC OLEH KAP HERU SATRIA RUKMANA DAN REKAN - Siti Sahoyah (2023)
Taxes are the largest source of state revenue. Value Added Tax is a type of tax that is a source of state revenue. Every entrepreneur who has been confirmed as a Taxable Entrepreneur has the obligation to calculate, deposit and report Value Added Tax. This final project report aims to analyze the suitability of the calculation, deposit and reporting of Value Added Tax based on the tax regulations that apply to PT ABC Employee Cooperatives. This final project report uses a qualitative method using secondary data in the form of input taxes, output taxes, tax invoices, Periodic VAT Returns and other data. In addition, data collection techniques used observation and documentation methods by collecting data directly by visiting the PT ABC Employee Cooperative office located in Bogor and documenting several supporting documents related to the object of writing this thesis. The results of writing this final project state that the PT ABC Employee Cooperative complies with current regulations in carrying out tax obligations for Value Added Tax for the 2022 period.